UPDATES ON CARDIOPULMONARY REANIMATION: REVIEW OF THE THEME, APPROACH OF THE NURSING TEAM AND NEW CONDUCTS IN THE FACE OF CARDIORESPIRATORY ARREST - Travasso, Cleiton; Silva Zborowski, Feliccia (Health and Society, 2023)
ardiorespiratory arrest is a major public health problem in the national context, which, if not addressed quickly and effectively, has high morbidity rates. The present study consists of a bibliographical research whose main objective is to characterize the profile of the emergency nurse, aiming to deepen the reflection on the subject. For this purpose, articles published according to the keywords and title found through electronic search were used. The practice of cardiopulmonary resuscitation has historically been the procedure of choice in primary care and represents a great tool to ensure the victim’s survival. However, even having firm theoretical bases, a large number of professionals fail at the time of practice and do not recognize their diagnosis, sequence of applicability and transition to advanced support. In addition, each year there are new updates and research on the methods already employed, configuring a scenario that becomes increasingly complex in terms of learning and its applicability. The objective of this study is to research the profile of professional nurses in approaching and facing cardiac arrests, their understanding in the field of urgency and emergency, the consequences and risks to which emergency nurses are exposed due to the performance of their work. This is a bibliographic review with a qualitative approach. In this study, the applied methodology was to choose the journals according to the theme and keywords.